Holdt tesen? - Thaning, Kaj (Grundtvig-Studier, 1966)
Did the Thesis Hold? By Kaj Thaning A. Pontoppidan Thyssen, D. D. - like K. E. Bugge, D. D. in his thesis Skolen for livet - has taken up a critical attitude towards my work Menneske først -Grundtvigs opgør med sig selv. P. Th.’s criticism appeared in print in Kirke historiske samlinger V, 3, 1965. He attacks my main thesis according to which the year 1832 marked the turning point in Grundtvig’s life, because it saw his conversion to “life and human nature” resulting in a clash with his earlier outlook on Christianity and a gradually advancing clarification in all fields as he came to devote his energy to the various tasks confronting him. P. Th. maintains that the development was more gradual, that much was anticipated before 1832, and that decisive matters were not clarified until later, just as self-contradictions still occur in his outlook. Further, I am supposed to have made use of modem concepts in such a way as to smooth out contradictions. As regards the objections to my treatment of the period before 1832 my answer will have to be deferred to a later work. Of course it is true that everything before 1832 conditions the clarification of that year. Without this basis there would have been no problem. But the solution to the problem manifested itself in 1832. Bugge’s thesis confirms my view of the outlook characteristic of Grundtvig’s home (the Lutheran Christianity of repentance or “a kind of pietism” ), and he documents what I have inferred from the (later) heart-searchings of Grundtvig. I agree with P. Th. that Grundtvig is still marked by this outlook, but one might well ask whether the accents of a Christianity of repentance in his preaching are not due to his dependence on the Bible (the literature of St. John; St. Paul). Grundtvig was faithful to the Bible. P. Th. will not accept that a “profane” discovery of human life (the impressions from England) may have a positive influence on a view of Christianity, but this is a theological prejudice in him. The fact is that in this way a false view of Christianity may be divested of demonism. It will then serve and not rule, because Christianity is no longer the great heavenly example to be followed in our management of the world (this was Grundtvig’s earlier view), but a defenceless Gospel. By Christianity in Lutheran dress Grundtvig’s problem (the relation between Christianity and human life) was raised, and strictly speaking it would be biographically correct in his case to say “first a Christian”. But it was the solution to the problem that conditioned as a matter of principle his “motto” : “first a human being” . P. Th. will not be convinced that Mrs. Clara Bolton was the original cause of clarification, but the evidence as presented in my book may receive further substantiation. P. Th. criticizes my use of the word “secularization” as a means of interpretation with regard to Grundtvig’s work— the mythology, the world history, the church history, and the chief treatise on church politics: “Den danske Statskirke” . But nowhere did I use the word in the modern sense equivalent to a wiping out of the importance of Christianity or the Church (“secularism” ). It is only a means to interpret Grundtvig’s own intention, since he now consciously wants to give up his earlier inclination to christianize culture, politics, enlightenment etc. which made Christianity rule and not serve. Thus he now secularizes his view of the “spirit” (as distinct from the Holy Ghost), the writting of history, his view of society, poetry, and the church institution which is now something different from the Holy Universal Church, namely a thing of this world. Accordingly, when writing ecclesiastical history he points out the purely human basis of the church. The history of the Word of God itself is obviously not secularized: it is not considered a human phenomenon. P. Th. is right, however, in finding less than sufficient comment in my book on some passages in “Den danske Statskirke” concerning certain statements about the necessity of Christianity to culture. By juxtaposing a series of quotations from the treatise on the continuation of the Lutheran reformation (1831), from the treatise on the State church, and from an unprinted draft: “Om statsmæssig Oplysning” (both from 1834) I try to throw light on the gulf between Grundtvig’s outlook in 1831 and 1834 respectively, and upon the continuity between 1832 and 1834. Before, the preacher saw in a normative Christianity the necessary means to the preservation of culture; now, with arguments of statesmanship the historian urges that the ancestral faith should remain within the State church as long as this is not made impossible by the introduction and enforcement of new, modernized rituals. That is to say, the arguments have become secularized. And freedom is now a condition if the ancestral faith is to give inspiration to cultural life. Culture is no longer to be reformed according to a lofty Christian ideal. Rather, the State should just see to it that faith is left alone to work its wonders, little or great. The essential thing is really for a free and competitive spirit within the State church to promote enlightenment and influence culture in a decisive way. Of course Grundtvig does not pursue his line of thought without some deviations, but these are more fortuitous than P. Th. is willing to admit. Throughout I have tried to find Grundtvig’s real aim and thus to emphasize what seems to me essential in his work. In my opinion his separation of human and Christian makes it possible for him as a clergyman to preach the unity of God and man: God’s salvation concerns human life, but human life is there before being addressed by the word of salvation. That is why the dissociation receives emphasis. To maintain, as P. Th. does, that Grundtvig wants to assert “at the same time” the connection and the distinction between human and Christian is therefore an abstraction. The separation is the condition of any talk of connection or “interaction” . P. Th. maintains that I interpret Grundtvig by modem concepts (secularizaiotion, existentialist philosophy, “de-mythicization” ) to arrive at a “living” Grundtvig; he would rather have a correct picture of the “historical” Grundtvig. That is just what I meant to give, however, partly by understanding his ideology in comparison with Irenæus, Schelling, and others, partly by not bringing modem concepts into his view but explaining how he “secularizes” (what other word is there?), how he reflects on the human condition (as distinct from the present) and places such an understanding of life “before” the hearing of the Gospel. And how he distinguishes between letter and spirit in this connection. If we do not keep the historical distance, he will cease to be a challenge. His heart-searchings still concern us. The historical Grundtvig is the living Grundtvig.